Реалити-шоу "Замок": роман / Ксения Баштовая - Баштовая Ксения Николаевна (Армада, 2009)
Экземпляры: ф.11 (20170904) / Инвентарный номер: 57356 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 33 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445